ADAPTIVE INSTRUCTIONAL LEADERSHIP IN RESOURCE-CONSTRAINED KINDERGARTENS: A QUALITATIVE STUDY OF PRINCIPALS’ STRATEGIES - Darwanti, Puji; Rochmawati, Nur Intan (Universitas Islam Negeri Mataram, 2026)
Instructional leadership plays a critical role in improving learning quality in early childhood education; however, its enactment in resource-constrained kindergarten settings remains underexplored. This study examines how kindergarten principals implement adaptive instructional leadership in contexts characterized by limited resources, heavy reliance on honorary teachers, and demanding curricular demands. Employing a qualitative descriptive–interpretive design, data were collected through semi-structured interviews, non-participant observations, and document analysis involving kindergarten principals, teachers, and early childhood education supervisors in resource-constrained kindergartens. Data were analyzed using an interactive thematic analysis approach guided by the Adaptive Instructional Leadership framework. The findings reveal five interrelated leadership strategies: (1) pragmatically framing instructional vision under resource constraints, (2) enacting context-responsive academic supervision, (3) facilitating school-based professional learning as a substitute for formal development, (4) mediating curriculum implementation through contextual adaptation, and (5) sustaining instructional quality through relational and collaborative leadership practices. These strategies demonstrate that instructional leadership in kindergartens operates as a dynamic and adaptive process rather than a standardized set of practices. This study contributes to instructional leadership theory by foregrounding adaptation and contextual responsiveness as central mechanisms of leadership in early childhood education. The findings offer theoretical insights and practical implications for leadership development and policy initiatives to strengthen instructional leadership capacity in resource-constrained kindergarten settings